2011
DOI: 10.1002/lary.21880
|View full text |Cite
|
Sign up to set email alerts
|

Phonation threshold pressure and flow in excised human larynges

Abstract: Objectives/Hypothesis 1. To determine the phonation threshold pressure (PTP) and phonation threshold flow (PTF) in excised human larynges. 2. To determine the effects of posterior glottal width, glottal area, and gender on PTP and PTF. 3. To test the hypothesis that hysteresis is present in excised human laryngeal phonation. 4. To compare these results to those from canine experiments and human subject measurements. Study Design Induced phonation of excised human larynges in the laboratory. Methods Nine hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…This is consistent with PTP ranges reported by Mau et al 19 for their offset PTP. The ranges of Ps, flow rate, and fundamental frequencies are also included in the table.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with PTP ranges reported by Mau et al 19 for their offset PTP. The ranges of Ps, flow rate, and fundamental frequencies are also included in the table.…”
Section: Discussionsupporting
confidence: 93%
“…Four weeks after laser injury, the animals were sacrificed and their larynges harvested. Four of the eight larynges were subjected to excised larynx phonation, which was induced as previously described . Subglottal airflow was slowly increased until audible phonation occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with physical models (Titze et al, 1995;Chan et al, 1997;Mau et al, 2011;Mendelsohn and Zhang, 2011), computer simulation models (Pickup and Thomson, 2011), and analytical calculations (Titze, 1988b;Lucero, 1998;Chan and Titze, 2006;Klemuk et al, 2010;Lucero et al, 2011;Fulcher et al, 2012) have shown that a near rectangular glottis (as viewed in the coronal plane) produces the lowest oscillation threshold pressure. (Direct measurement of this configuration in human subjects has not been reported.)…”
Section: A Criterion For Optimal Adductionmentioning
confidence: 99%